Clinical and Ultrasonographic Remission in Bio-naïve and Bio-failure Patients with Rheumatoid Arthritis at 24 Weeks of Upadacitinib Treatment: The UPARAREMUS Real-Life Study - Andrea Picchianti Diamanti; Maria Sofia Cattaruzza; Simonetta Salemi; Roberta Di Rosa; Giorgio Sesti; Chiara De Lorenzo; Gloria Maria Felice; Bruno Frediani; Caterina Baldi; Maria Sole Chimenti; Arianna D’Antonio; Gloria Crepaldi; et al. (Rheumatology and Therapy, 2024)
Abstract Introduction Clinical remission is the main target in the management of patients with rheumatoid arthritis (RA). However, several authors found synovitis in patients with RA in clinical remission at ultrasonography (US). Upadacitinib is a selective Janus kinase 1 inhibitor that achieved significantly higher remission rates than adalimumab and abatacept in patients with RA. Here we present the 24-week data of the UPAdacitinib Rheumatoid Arthritis REmission UltraSonography (UPARAREMUS) study. Methods This is a longitudinal multicenter observational study, enrolling bio-naïve and bio-inadequate responder patients affected by RA. The primary endpoint was the proportion of patients achieving both clinical and US remission at week 24. The proportion of patients achieving clinical remission with different composite indexes at week 12 and 24 was also evaluated. US of four target joints (wrists and second metacarpophalangeal bilaterally) was performed at baseline and weeks 12/24, and US remission was defined as the absence of power Doppler (PD) signal ≥ 2 in one target joint, or PD ≥ 1 in two target joints. Results After 12 weeks and 24 weeks, 40% and 63.6% of patients achieved US plus clinical remission. The following parameters were associated with US plus clinical remission: being bio-naïve and having a shorter disease duration, although at multivariate analysis significant odds ratio (OR) was found only for being bio-naïve. Conclusions UPARAREMUS is the first study evaluating the efficacy of upadacitinib in reaching both clinical and US remission in patients with RA. At 24 weeks, 63.6% of patients reached the primary endpoint, the only baseline associated parameter was being bio-naïve.